The wild bees (Hymenoptera: Apoidea) of Morocco - Lhomme, Patrick; Michez, Denis; Christmann, Stefanie; Scheuchl, Erwin; Abdouni, Insafe El; Hamroud, Laila; Ihsane, Oumayma; Sentil, Ahlam; Smaili, Moulay Chrif; Schwarz, Maximilian; Dathe, Holger H.; Straka, Jakub; et al. (Zootaxa, 2020)
Morocco is a well known hot-spot of biodiversity in the Mediterranean basin. While some taxa like vascular plants are relatively well recorded, important groups of pollinators like bees are still understudied. This article presents an updated checklist of the bee species of Morocco and includes a summary of global and regional distribution of each species. A total of 961 species belonging to six bee families and 68 genera are recorded: Andrenidae (8 genera, 217 species); Apidae (15 genera, 241 species); Colletidae (2 genera, 74 species), Halictidae (12 genera, 144 species), Megachilidae (28 genera, 271 species) and Melittidae (3 genera, 14 species). Among them, 67 species are recorded for the first time in Morocco. Around 70% of the bee fauna of Morocco consists of widespread Palaearctic species. Only 18% of Moroccan species recorded are restricted to North Africa and 8% are Moroccan single-country endemics (81 species). Afrotropical elements in the Moroccan fauna are few, with only 3% of Morocco species co-occuring in that region. This checklist is intended to stimulate new regional research on bees including their taxonomy and biogeography. As many groups of bees have been understudied, discovery of new species for science and new records for the country can be expected. Additional research including inventorying, monitoring, and integrative taxonomic studies are needed to develop a comprehensive strategy for bee conservation in Morocco.